Topside Ionosphere During the Mother's Day Superstorm as Observed by Multiple LEO Spacecraft, Including SNIPE - Hosub Song; Jaeheung Park; Jaejin Lee; Tae‐Yong Yang; Jongdae Sohn; Young‐Sil Kwak; Yukinaga Miyashita; Youngbum Song; Ki‐Hwan Keum; Chae‐Ryeong Kim; Yu Yi; Magnus Ivarsen; et al. (Space Weather)
Abstract We analyze the topside electron density and temperature during the superstorm in May 2024 (Mother's Day storm or Gannon storm), using multiple Low‐Earth Orbit (LEO) spacecraft operating at different altitudes, such as Swarm, International Space Station, Defense Meteorological Satellite Program, Polar Operational Environmental Satellites, and the Small‐scale magNetospheric and Ionospheric Plasma Experiment (SNIPE). The SNIPE mission was designed to investigate micro‐scale plasma structures in Earth's ionosphere and magnetosphere. The SNIPE constellation was launched on 25 May 2023, and continues to operate in a dawn‐dusk Sun‐synchronous orbit at an altitude of approximately 530–550 km. In this paper, we report significant changes in topside electron density and temperature, measured by SNIPE. Furthermore, SNIPE observations are compared with independent ground‐based Total Electron Content measurements and data from other LEO satellites. Three characteristics of the data are highlighted. First, we address the unusual expansion of the Equatorial Ionization Anomaly around the magnetic equator and its hemispheric asymmetry, which is dependent on altitude. Second, a large Tongue of Ionization in the polar region extends to ∼840 km above the ground, accompanied by a weak decrease in electron temperature. Third, we report electron temperature enhancement near the auroral zones across a wide range of local times, which partially overlaps with energetic particle precipitation. These three results complement existing studies of the Mother's Day/Gannon geomagnetic storm.